(untitled) - Sassone, Peter G. (New York, 1978)
This book is addressed to practicing cost-benefit analysts, to government officials who commission, oversee, and use cost-benefit studies, to citizens who wish to understand tho workings of an analysis that may recommend turning their favorite trout stream into a lake,....
Keywords: Cost effectiveness,Hiệu quả chi phí